2012
DOI: 10.1016/j.jmarsys.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the planktonic community structure related to trophic conditions: The case study of the northern Adriatic Sea

Abstract: Fuks Dragica et all. Changes in the planktonic community structure related to trophic conditions: The case study of the northern Adriatic Sea Journal of marine systems, 96-97 (2012), 4; 95-102 Introduction 30One of the important aims of the community ecology is the understanding of 31 carbon flux through the trophic levels. There is evidence that the transfer of organic 32 carbon through the trophic levels differs between regions with diverse productivity. 33The plankton from unproductive regions is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…On the other hand, nitrate concentrations were higher than in the aforementioned studies implying different structure of the nutrient pool between these two basins. The concentrations of measured nutrients at the Farm are comparable with the values commonly found in the Adriatic Sea for the locations that are not under the aquaculture influence (Ivančić, Fuks, Najdek, Blažina, Devescovi, Šilović, Paliaga & Orlić ; Fuks, Ivančić, Najdek, Lučić, Njire, Godrijan, Marić, Šilović, Paliaga, Blažina, Precali & Orlić ; Šantić, Šestanović, Šolić, Krstulović, Kušpilić, Ordulj & Ninčević ). Thus, the general assumption that continuous nutrient loadings from fish farms could have serious effects on natural occurring nutrient concentrations, particularly in the oligotrophic environment does not appear to be the case here.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, nitrate concentrations were higher than in the aforementioned studies implying different structure of the nutrient pool between these two basins. The concentrations of measured nutrients at the Farm are comparable with the values commonly found in the Adriatic Sea for the locations that are not under the aquaculture influence (Ivančić, Fuks, Najdek, Blažina, Devescovi, Šilović, Paliaga & Orlić ; Fuks, Ivančić, Najdek, Lučić, Njire, Godrijan, Marić, Šilović, Paliaga, Blažina, Precali & Orlić ; Šantić, Šestanović, Šolić, Krstulović, Kušpilić, Ordulj & Ninčević ). Thus, the general assumption that continuous nutrient loadings from fish farms could have serious effects on natural occurring nutrient concentrations, particularly in the oligotrophic environment does not appear to be the case here.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the carbon budget of this period can be considered as a suitable baseline in order to (i) verify the possibility of the northern Adriatic Sea acting as a “continental shelf pump” for CO 2 sequestration, from the combined effect of solubility and biological pumps, and (ii) define the degree of eutrophication that sometimes occurs during spring‐summer. Among the few studies about this topic, some researches of the microbial C biogeochemistry showed different trophic regimes in different areas and seasons [ Giani et al ., ; La Ferla et al ., , , ; Fonda Umani et al ., ; Fuks et al ., ]. During the PRISMA 2 project (1996–1998), the trophic balance appeared to move toward autotrophy in winter when a positive C budget resulted.…”
Section: Discussionmentioning
confidence: 99%
“…Fuks et al . [] found that, both under oligotrophic conditions and in eutrophic events, chl‐ a ‐derived biomass in the northern Adriatic Sea was always higher than the prokaryotic one, the two being almost equal only at surface during oligotrophic conditions. In the Gulf of Trieste (the northeastern part of northern Adriatic Sea), Fonda Umani et al .…”
Section: Discussionmentioning
confidence: 99%
“…A high abundance of prokaryotes and faecal indicator bacteria was present in these waters. Such concentrations were more than twenty times higher than at an unpolluted referent station [40,41]. The ratio of FC/FS ~1 indicated the prevalence of a non-human source for these bacteria [42] since the cannery effluent contained exclusively fish remains and waste from fish processing.…”
Section: Discussionmentioning
confidence: 99%